One‐dimensional growth of colloidal PbSe nanorods in chloroalkanes. Issue 11 (5th October 2016) - Kandel, Shreedhar R.; Chiluwal, Shailendra; Jiang, Zhoufeng; Tang, Yiteng; Roland, Paul J.; Subedi, Kamal; Dimick, Douglas M.; Moroz, Pavel; Zamkov, Mikhail; Ellingson, Randy; Hu, Jianjun; Voevodin, Andrey A.; et al.
Abstract : Catalyst‐free, one‐pot synthesis of colloidal PbSe nanorods is demonstrated. The co‐solvent chloroalkanes play a critical role in driving a one‐dimensional growth of PbSe nanorods. The formation of the nanorod is likely governed by the anisotropic growth of the crystal due to the different reactivity of the facets. The photoluminescence quantum yield of the nanorods is above 25%, indicating well‐passivated surfaces. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : One‐dimensional growth of colloidal PbSe nanorods can be driven by a chloroalkane co‐solvent which likely modifies the reactivity of different facets. Synthesized nanorods have a high photoluminescence quantum yield above 25%, and their energy gap (diameter) can be tuned broadly by changing the reaction temperature, which is important for their applications in optoelectronics and thermoelectrics.